2021
DOI: 10.1038/s41598-021-91932-7
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy of mucin granules contributes to resolution of airway mucous metaplasia

Abstract: Exacerbations of muco-obstructive airway diseases such as COPD and asthma are associated with epithelial changes termed mucous metaplasia (MM). Many molecular pathways triggering MM have been identified; however, the factors that regulate resolution are less well understood. We hypothesized that the autophagy pathway is required for resolution of MM by eliminating excess non-secreted intracellular mucin granules. We found increased intracellular levels of mucins Muc5ac and Muc5b in mice deficient in autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 76 publications
(108 reference statements)
1
10
0
Order By: Relevance
“…Some scholars have reported that the intracellular mucin particles in the airway epithelial cells are reduced by inhibiting the activation of mTOR, and further studies have verified this result in patients with asthma and COPD (Sweeter et al. 2021 ). In the asthmatic mice in the present study, PAS staining identified mucus secretion around the small airway, which may be consistent with the increased expression levels of mTOR and p-mTOR.…”
Section: Discussionmentioning
confidence: 93%
“…Some scholars have reported that the intracellular mucin particles in the airway epithelial cells are reduced by inhibiting the activation of mTOR, and further studies have verified this result in patients with asthma and COPD (Sweeter et al. 2021 ). In the asthmatic mice in the present study, PAS staining identified mucus secretion around the small airway, which may be consistent with the increased expression levels of mTOR and p-mTOR.…”
Section: Discussionmentioning
confidence: 93%
“…mTOR activation is upstream of autophagy in airway epithelial cells: We previously have shown that hAECs and mice deficient in autophagy have increased cytoplasmic MUC5AC levels (20,23). To determine the relationship between mTOR signaling and autophagy during development and airway mucous metaplasia, we used mouse airway epithelial cells (mAECs) derived from Atg16L1 sufficient wildtype (WT) or Atg16L1 deficient mouse tracheas (Atg16L1 HM/HM ) cultured under ALI conditions with mouse recombinant IL-13 for 14 days (Fig.…”
Section: B Ementioning
confidence: 99%
“…Autophagy plays a role in exacerbating the development of asthma. Sweeter et al reported that Atg16 hypomorphic mice with IL-33-induced airway inflammation have decreased goblet cell hyperplasia ( Sweeter et al, 2021 ). Consistent with this finding, LC3-deficient mice showed a reduction in HDM-induced airway inflammation and reduced mucus secretion ( Li et al, 2020 ).…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%